APLIKASI INVENTARISASI DATA SPASIAL BERBASIS WEB GIS (STUDI KASUS: KOTA BENGKULU) - Rusdi Efendi (JURNAL AKADEMIKA)
Main purpose of this research is to build a web GIS based application of spatial data inventory which facilitate user to manage spatial data in an integrated way. With this software, user could save, edit, and show spatial data through web environtment without performing web GIS development. The method that was used on system development is waterfall model of SDLC (System Development Life Cycle). Modeling analysis and system design was using UML (Unified Modeling Language). The result of analisys and system design then be implemented through PHP (Hypertext Processor) language, and MySQL (My Structured Query Language). This software has ability to extract digital data in GML (Geographic Markup Language) format, save spatial data in WKT (Well- Known Text) Format, and show spatial data in vector format which completed by legend and some facilities, such as: zoom in, zoom out, zoom to max extent, layer switcher, scale, scale line, mouse position, drawing tools, and popup window. According the test that has been performed, system could handle spatial data management which including: saving and showing spatial data in vector format.